Working out of receptions of bioremediation masout sewage - A. R. Galperina (Юг России: экология, развитие, 2015)
Hydrochemical and microbiological analysis of residual masout sewage was carried out. It was revealed that the native microflora takes active part in biodegradation of oil hydrocarbons. Injection of cyano-bacterial communities and water plants activates processes of self-cleaning of sewage from oil products. About this testify a decrease of total oil hydrocarbons – on 98%; optical density – on 71%.